OP59 Do Demands and Worries from Close Social Relations Increase the Risk of Subsequent Incident IHD Hospitalization? A 7 Year Longitudinal Study of Middle-Aged Danish Men and Women. (17th September 2012) - Lund, R; Rod, NH; Thielen, K; Christensen, U
Abstract : Background: The association between support from social relations and ischemic heart disease is well described, however the possible hazardous effects of negative aspects of social relations on cardiovascular health are less well known. The purpose of the present study was to analyze the possible influence of negative aspects of social relations (NASR) at baseline on the risk of development of ischemic heart disease (IHD) defined as incident hospitalized cases of acute myocardial infarction and chronic IHD during 7 year follow-up. NASR were defined as demands or worries from partner, children, family, and friends. Methods: Participants were included in a questionnaire-based study in 2000 and were a random sample (N=6767) of Danish men and women aged 40 or 50 years by October 1st 1999 from the Danish Longitudinal Study on Work, Unemployment and Health. Data for the present study are based on baseline questionnaire data in 2000 and register linked data from the period 2000–2007 on hospitalization for IHD (ICD10: I21–25). Cases of IHD (I21–25) four years prior to baseline were excluded from the analyses. In total 127 new cases of IHD were identified during follow-up. Results: Men who always or often experienced worries or demands from their partner had an increased risk of incident IHD compared to those who seldom/never experienced worries and demands HR(95%CI)=2.28(1.14–4.53) adjusted for age, socioeconomic status, cohabitation status, depressive symptoms, smoking and emotional support from all social relations . There was no association between demands/worries from partner and risk of development of IHD among women. Both men and women who experienced frequent worries and demands from their family (other than partner and children) were at increased risk of IHD HR=1.76(1.10–2.81) adjusted for above mentioned covariates and gender. Demands and worries from children and friends were not associated with significantly increased risk of IHD although estimates were in the same direction as for demands/worries from partner and family. Conclusion: For men, frequent demands and worries from a partner seem to be associated with increased risk of incident IHD hospitalization during 7 year follow-up. Demands/worries from family are risk factors for both women and men. Adjustment for the level of social support from all social relations did not change these conclusions. These findings confirm earlier findings of an association between NASR and self-reported angina pectoris. The weaker findings for women may partly be explained by the substantially smaller number of cases in this middle-aged cohort.